Survival after 131I-labeled lipiodol therapy for hepatocellular carcinoma - Ahmadzadehfar, H.; Habibi, E.; Ezziddin, S.; Wilhelm, K.; Fimmers, R.; Spengler, U.; Palmedo, H.; Strunk, H.; Schild, H. H.; Biersack, H. J.; Risse, J. (Nuklearmedizin - NuclearMedicine, 2014)
This study investigated the efficacy of 131iod- ine-labeled lipiodol (1311-lipiodol) as a palliative therapy, evaluated overall survival (OS) across Barcelona Clinic Liver Cancer (BCLC) stages, and determined the main prognostic factors influencing OS in patients with hepatocellular carcinoma (HCC). Patients, methods: We retrospectively analyzed 57 (44 men; mean age, 65.7 years; mean activity per session, 1.6 GBq; mean cumulative activity in patients with >1 sessions, 3.9 GBq) HCC patients who underwent 1311-lipiodol therapy. A majority of patients exhibited Child-Pugh class B (53.6%) disease and a good Eastern Cooperative Oncology Group performance status (0-1; 72%). Multinodular disease was observed in 87.7% patients, bilobar disease in 73%, and portal vein occlusion (PVO) in 54%. Furthermore, 21.1% patients were staged as BCLC B and 59.6 % as BCLC C. All patients were followed until death. Results: The median OS was 6.4 months, which varied significantly with disease stage (median OS for BCLC A, B, C, and D was 29.4, 12.0, 4.6, and 2.7 months, respectively; p = 0.009); Child-Pugh score and class; presence of ascites, PVO, or extrahepatic disease; largest lesion size; favourable treatment response; international normalized ratio, baseline albumin and alpha-fetopro- tein levels. Patients with a Child-Pugh A liver disease had a longer OS. Conclusion: Currently, different treatment modalities for HCC include radioembolization, transarterial chemoemboliz- ation, and systemic therapy with sorafenib; however, 1311-lipiodol therapy remains a feasible alternative for patients without a favourable response to other therapies, particularly for patients with Child-Pugh A liver cirrhosis.
Keywords: Liver cancer; hepatocellular carcinoma; radionuclide therapy; 131I-lipiodol; BCLC